Challenges in the use of sortase and other peptide ligases for site-specific protein modification - Holly E. Morgan; W. Bruce Turnbull; Michael E. Webb (2022)
We highlight chemical and biochemical strategies taken to optimise peptide and protein modification using peptide ligases.